DOI: 10.11606/d.64.2015.tde-05052015-101840
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da macaúba (casca, polpa e amêndoa) e análise sensorial através da Educação do Gosto

Abstract: Caracterização da macaúba (casca, polpa e amêndoa) e análise sensorial através da Educação do Gosto Piracicaba 2015 1 SAMUEL ZANATTA Caracterização da macaúba (casca, polpa e amêndoa) e análise sensorial através da Educação do Gosto Versão revisada de acordo com a Resolução CoPGr 6018 de 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…Table 1 summarizes the results of the chemical composition of the flours analyzed. Results of MC flour for moisture, ashes, and crude fiber are similar to the reported in the literature (Kopper et al, 2009;Verediano, 2012;Zanatta, 2015), however, fat content was considerably lower, which can be explained for differences in the oil extraction procedure. The variation between protein and carbohydrate contents can be related to the different methodologies used to obtain the flours and to the natural variability of the fruits.…”
Section: Chemical Composition Of the Flourssupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1 summarizes the results of the chemical composition of the flours analyzed. Results of MC flour for moisture, ashes, and crude fiber are similar to the reported in the literature (Kopper et al, 2009;Verediano, 2012;Zanatta, 2015), however, fat content was considerably lower, which can be explained for differences in the oil extraction procedure. The variation between protein and carbohydrate contents can be related to the different methodologies used to obtain the flours and to the natural variability of the fruits.…”
Section: Chemical Composition Of the Flourssupporting
confidence: 87%
“…The values of L* and a* are very close to those determined in this study and the differences between b* and H° values can be explained because MC was submitted to an additional process of drying and extraction of lipids that may lead to the removal of substances responsible for yellow and/or orange coloration such as β-carotene. Also, Zanatta (2015) investigating the color of macauba fruit pulps observed that samples that were exposed to mechanical processes become darker with increasing process temperature. The author also highlighted…”
Section: Colormentioning
confidence: 99%
“…The production of activated carbon from residual lignocellulosic biomass is presented in the flowchart. After the macaúba fruit peeling process, the peels undergo a drying process in an oven at 60 °C for 12 hours (ZANATTA, 2015). This step is important for the volatilization of compounds such as water from the structure of the material that will be used in the production of activated carbon (SCHETTINO et al, 2007).…”
Section: Activated Charcoalmentioning
confidence: 99%
“…Alguns estudos sobre o óleo extraídos da polpa e da amêndoa da bocaiuva, do buriti e do pequi. Alguns avaliaram os métodos de extração (ALVES et al, 2012;NUNES, 2013); outros autores avaliaram as propriedades físicas e químicas (ZANATTA, 2015;AQUINO et al, 2012;RIBEIRO, 2010;AMARAL, 2007…”
Section: Agradecimentosunclassified